Self‐care behaviour for minor symptoms: can Andersen's Behavioral Model of Health Services Use help us to understand it?. (15th April 2014) - Porteous, Terry; Wyke, Sally; Hannaford, Philip; Bond, Christine
Abstract Objective To explore whether Andersen's Behavioral Model of Health Services Use can aid understanding of self‐care behaviour and inform development of interventions to promote self‐care for minor illness. Method Qualitative interviews were conducted with 24 Scottish participants about their experience and management of minor symptoms normally associated with analgesic use. Synthesised data from the interviews were mapped onto the Behavioral Model. Key findings All factors identified as influencing decisions about how to manage the symptoms discussed, mapped onto at least one domain of Andersen's model. Individual characteristics including beliefs, need factors and available resources were associated with health behaviour, including self‐care. Outcomes such as perceived health status and consumer satisfaction from previous experience of managing symptoms also appeared to feed back into health behaviour. Conclusions The Behavioral Model seems relevant to self‐care as well as formal health services. Additional work is needed to explore applicability of the Behavioral Model to different types of symptoms, different modalities of self‐care and in countries with different health care systems. Future quantitative studies should establish the relative importance of factors influencing the actions people take to manage minor symptoms to inform future interventions aimed at optimising self‐care behaviour.